The local GLP-1 system in the olfactory bulb is required for odor-evoked cephalic phase of insulin release in mice - Mireia Montaner; Jessica Denom; Wanqing Jiang; Christophe Magnan; Stefan Trapp; Hirac Gurden (Elsevier, 2023)
Objective: The olfactory bulb (OB) codes for sensory information and contributes to the control of energy metabolism by regulating foraging and cephalic phase responses. Mitral cells are the main output neurons of the OB. The glucagon-like peptide-1 (GLP-1)/GLP-1 receptor (GLP-1R) system in the OB (GLP-1OB) has been shown to be a major regulator of mitral cell activity but its function in vivo is unclear. Therefore, we investigated the role of GLP-1OB in foraging behavior and odor-evoked Cephalic Phase Insulin Release (CPIR). Methods and results: By fluorescent labeling, we confirmed the presence of GLP-1 producing neurons and the expression of GLP-1R in the mouse OB. In response to food odor presentation, we collected blood, quantified plasma insulin by ELISA and showed the existence of an odor-evoked CPIR in lean mice but its absence in obese animals. Expression of shRNA against preproglucagon mRNA in the OB resulted in blunted CPIR in lean mice. Injecting Exendin (9-39), a GLP-1R antagonist, into the OB of lean mice also resulted in decreased CPIR. Since parasympathetic cholinergic input to the pancreas is known to be partly responsible for CPIR, we systemically administered the muscarinic M3 receptor antagonist 4-DAMP which resulted in a reduced odor-evoked CPIR. Finally, local injection of Exendin (9-39) in the OB extinguished olfactory foraging in lean mice whereas the injection of the GLP-1R agonist Exendin-4 rescued the loss of foraging behavior in obese mice. Conclusions: Our results demonstrate that GLP-1OB controls olfactory foraging and is required for odor-evoked CPIR. We describe a new crucial brain function for GLP-1 and GLP-1R expressed within the brain.